INOVASI PEMANFAATAN PLATFORM DIGITAL TERBUKA UNTUK PEMBELAJARAN PAI ABAD 21 - Izzatuzzahroh; Junia Putri, Ismarani; Irsyad Saifullah, Muhammad; Harto, Kasinyo; Putra Pratama, Irja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic Religious Education (IRE) in the 21st century faces significant challenges in remaining relevant amid rapid advancements in digital technology and shifts in student demographics, which are now dominated by Generation Z and Generation Alpha. This article aims to analyze innovations in the utilization of open digital platforms as instruments for transforming content and character in PAI learning. Using the Systematic Literature Review (SLR) research method, this article reviews literature from reputable journals (Sinta and Scopus) over the past ten years. The SLR stages include source identification, literature screening based on inclusion criteria, assessment of material suitability, and inclusion of relevant data. The results indicate that open digital platforms such as Google Classroom, Canva, YouTube, and Quizizz have transformed PAI learning patterns from a rigid normative-transmissive approach to an interactive constructive-reflective one. The findings indicate that the integration of interactive multimedia can increase learning motivation by up to 86% and cognitive learning outcomes by 86.5%. In addition to serving as a visual aid, digital platforms play a role in internalizing Islamic character values through the development of digital literacy, communication ethics (digital etiquette), and the strengthening of critical thinking regarding information (tabayyun). This article concludes that the transformation of Islamic Education in the digital age requires a balance between educators’ technological competencies and oversight of spiritual content to produce a generation that is intellectually intelligent and morally sound.